The Effect of Audiovisual and Binaural Listening on the Acceptable Noise Level (ANL): Establishing an ANL Conceptual Model - Wu, Yu-Hsiang; Stangl, Elizabeth; Pang, Carol; Zhang, Xuyang (Journal of the American Academy of Audiology, 2014)
Background: Little is known regarding the acoustic features of a stimulus used by listeners to determine the acceptable noise level (ANL). Features suggested by previous research include speech intelligibility (noise is unacceptable when it degrades speech intelligibility to a certain degree; the intelligibility hypothesis) and loudness (noise is unacceptable when the speech-to-noise loudness ratio is poorer than a certain level; the loudness hypothesis).Purpose: The purpose of the study was to investigate if speech intelligibility or loudness is the criterion feature that determines ANL. To achieve this, test conditions were chosen so that the intelligibility and loudness hypotheses would predict different results. In Experiment 1, the effect of audiovisual (AV) and binaural listening on ANL was investigated; in Experiment 2, the effect of interaural correlation (ρ) on ANL was examined.Research Design: A single-blinded, repeated-measures design was used.Study Sample: Thirty-two and twenty-five younger adults with normal hearing participated in Experiments 1 and 2, respectively.Data Collection and Analysis: In Experiment 1, both ANL and speech recognition performance were measured using the AV version of the Connected Speech Test (CST) in three conditions: AV-binaural, auditory only (AO)-binaural, and AO-monaural. Lipreading skill was assessed using the Utley lipreading test. In Experiment 2, ANL and speech recognition performance were measured using the Hearing in Noise Test (HINT) in three binaural conditions, wherein the interaural correlation of noise was varied: ρ = 1 (NoSo [a listening condition wherein both speech and noise signals are identical across two ears]), −1 (NπSo [a listening condition wherein speech signals are identical across two ears whereas the noise signals of two ears are 180 degrees out of phase]), and 0 (NuSo [a listening condition wherein speech signals are identical across two ears whereas noise signals are uncorrelated across ears]). The results were compared to the predictions made based on the intelligibility and loudness hypotheses.Results: The results of the AV and AO conditions appeared to support the intelligibility hypothesis due to the significant correlation between visual benefit in ANL (AV re: AO ANL) and (1) visual benefit in CST performance (AV re: AO CST) and (2) lipreading skill. The results of the NoSo, NπSo, and NuSo conditions negated the intelligibility hypothesis because binaural processing benefit (NπSo re: NoSo, and NuSo re: NoSo) in ANL was not correlated to that in HINT performance. Instead, the results somewhat supported the loudness hypothesis because the pattern of ANL results across the three conditions (NoSo ≈ NπSo ≈ NuSo ANL) was more consistent with what was predicted by the loudness hypothesis (NoSo ≈ NπSo < NuSo ANL) than by the intelligibility hypothesis (NπSo < NuSo < NoSo ANL). The results of the binaural and monaural conditions supported neither hypothesis because (1) binaural benefit (binaural re: monaural) in ANL was not correlated to that in speech recognition performance, and (2) the pattern of ANL results across conditions (binaural < monaural ANL) was not consistent with the prediction made based on previous binaural loudness summation research (binaural ≥ monaural ANL).Conclusions: The study suggests that listeners may use multiple acoustic features to make ANL judgments. The binaural/monaural results showing that neither hypothesis was supported further indicate that factors other than speech intelligibility and loudness, such as psychological factors, may affect ANL. The weightings of different acoustic features in ANL judgments may vary widely across individuals and listening conditions.
Keywords: Acceptable noise level; audiovisual; binaural; interaural correlation